Community Health Representative Workforce: Meeting the Moment in American Indian Health Equity - Sabo, Samantha; O'Meara, Louisa; Russell, Kim; Hemstreet, Corey; Nashio, J. T.; Bender, Brook; Hamilton, Joyce; Begay, Mae-Gilene (Frontiers in Public Health, 2021)
In 2018, the Community Health Representative (CHR) workforce celebrated their 50th year and serve as the oldest and only federally funded Community Health Worker (CHW) workforce in the United States. CHRs are a highly trained, well-established standardized workforce serving the medical and social needs of American Indian communities. Nationally, the CHR workforce consists of 1,700 CHRs, representing 264 Tribes. Of the 22 Tribes of Arizona, 19 Tribes operate a CHR Program and employ 250 CHRs, equivalent to 30% of the total CHW workforce in the state. Since 2015, Tribal CHR Programs of Arizona have come together for annual CHR Policy Summits to dialogue and plan for the unique issues and opportunities facing CHR workforce sustainability and advancement. Overtime, the Policy Summits have resulted in the Arizona CHR Workforce Movement, which advocates for inclusion of CHRs in state and national level dialogue regarding workforce standardization, certification, training, supervision, and financing. This community case study describes the impetus, collaborative process, and selected results of a 2019–2020 multi-phase CHR workforce assessment. Specifically, we highlight CHR core roles and competencies, contributions to the social determinant of health and well-being and the level to which CHRs are integrated within systems and teams. We offer recommendations for strengthening the workforce, increasing awareness of CHR roles and competencies, integrating CHRs within teams and systems, and mechanism for sustainability.